Ramadan fasting and voluntary fasting: potential weight loss and weight maintenance opportunity for overweight and obese Muslims - Ismail, Suriani; Shamsuddin, Khadijah; Abdul Latiff, Khalib; Abu Saad, Hazizi; Abdul Majid, Latifah (Community Health Society Malaysia, 2014)
Religious teachings are potential health-promoting tools as religion is an imperative part of an individual‘s lifestyle. Health promoters should identify religious teachings which match the intended health objectives and innovatively package them to be acceptable yet effective. In the context of the proposed Islamic-based intervention, the intended behaviour change is fasting. Fasting can control total energy intake and thus correct energy imbalance in overweight and obese persons. The health objectives are to obtain a significant initial weight loss during Ramadan and to maintain the weight loss by practicing Islamic voluntary fasting after Ramadan. Significant initial weight loss and adherence to treatment are positive predictors for sustained weight loss. Intervention that is religiously suitable would be more acceptable and thus more effective.